2006
DOI: 10.1152/japplphysiol.00440.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hormone responses following light resistance exercise with partial vascular occlusion and moderately difficult resistance exercise without occlusion

Abstract: Previous studies of contracting muscle with low loading and partial vascular occlusion demonstrated hypertrophy and strength adaptations similar to and exceeding those observed with traditional moderate to high resistance (Shinohara M, Kouzaki M, Yoshihisa T, and Fukunaga T. Eur J Physiol 77: 189-191, 1998; Takarada Y, Takazawa H, Sato Y, Takebayashi S, Tanaka Y, and Ishii N. J Appl Physiol 88: 2097-2106, 2000; Takarada Y, Sato Y, and Ishii N. Eur J Physiol 86: 308-314, 2002). The purpose of the study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
136
5
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 37 publications
(46 reference statements)
11
136
5
18
Order By: Relevance
“…However, during the BFR condition, the time course of the lactate response indicated that metabolites were retained and had accumulated in the working muscle. This finding was similar to Reeves et al (76), who compared low--intensity (30% of 1RM) elbow flexion and plantar flexion with BFR (cuff pressure set at 20 mm Hg below resting systolic pressure for upper body and 40 mm Hg above upper body occlusive pressure; cuff width not reported) to moderate intensity without BFR (70% of 1RM) and found equivalent lactate responses, albeit a larger GH response in the low intensity with BFR condition. This would seem to indicate that lactate (and the associated metabolic acidosis) is not the only modulator of the GH response to BFR exercise.…”
Section: Endocrine Responsessupporting
confidence: 89%
See 3 more Smart Citations
“…However, during the BFR condition, the time course of the lactate response indicated that metabolites were retained and had accumulated in the working muscle. This finding was similar to Reeves et al (76), who compared low--intensity (30% of 1RM) elbow flexion and plantar flexion with BFR (cuff pressure set at 20 mm Hg below resting systolic pressure for upper body and 40 mm Hg above upper body occlusive pressure; cuff width not reported) to moderate intensity without BFR (70% of 1RM) and found equivalent lactate responses, albeit a larger GH response in the low intensity with BFR condition. This would seem to indicate that lactate (and the associated metabolic acidosis) is not the only modulator of the GH response to BFR exercise.…”
Section: Endocrine Responsessupporting
confidence: 89%
“…Numerous studies have found that the ischemic (88) and hypoxic (92) intramuscular environment associated with BFR protocols induces a greater rate of ATP hydrolysis, exaggerated PCr depletion (85) decreased pH (84,85), and an increased lactate response (26,74,76,88,89). Suga et al (84) found greater metabolic stress (i.e., PCr, Pi, and deprotonated phosphate) via 31P--magnetic resonance spectroscopy, during low--intensity exercise (20% of 1RM) with BFR (varying pressure; 18.5--cm cuff width) vs. lowintensity (20% of 1RM) without BFR.…”
Section: Metabolic Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…No nosso estudo, ficou evidente que o treino sob oclusão vascular induziu aumentos significativos do lactato sanguíneo em diferentes momentos (meio e final do treino) quando comparados aos valores basais, bem como no grupo que treinou sob alta intensidade, que apesar de não ter sido observada a significância, observou-se valores altos de lactato. Em um estudo conduzido por (Reeves et al, 2006), as concentrações de lactato foram similares no grupo submetido ao treino com oclusão vascular e também no grupo que treinou com resistência moderada sem oclusão. Porém, as concentrações de GH foram maiores no grupo que treinou sob oclusão.…”
Section: Análise Estatísticaunclassified